Mengatasi Substitusi Menulis Permulaan melalui Metode VAKT bagi Anak Tunagrahita Ringan Kelas IV di SDLB Negeri 20 kota Pariaman (Single Subject Research Kelas IV di SDLB Negeri 20 kota Pariaman) - Rifda Juwita Rizal; Fatmawati Fatmawati; Martias Z (Jurnal Penelitian Pendidikan Khusus, 2013)
This research of background by the problems which is researcher find in SDLBN 20 Pariaman cities, a child of intelegance below X can not write properly starters, child change characters (substitution) in writing. Based on this research the mentioned aim to overcome replacement of characters (substitution) and see method effectiveness of VAKT in overcoming the problems. This research uses the methods of experimental research Single Subject Research (SSR) with the A-B design. This subject research child of intelegance below X class IV. Assessment in this research consistence and measure the number correct answers written by children in the beginning of writing start (specially writing characters which is child substitution, writing a word consisting of two and three syllables) given by treatment and presenting in the form of number. Result of this research indicate that, ability of child of intelegance below X in writing start beginning of writing after given by treatment and are no longger replacing characters (substitution). In the baseline condition (A) made six observations of the child can only write correctly five instruments, namely characters lt, rt, bp, bapak, and larutan. In the intervention condition (B) ) which is ten times treatment with perception of ability of child progressively beginning of writing that is can write truly all instrument which is researcher give. Finally child can write start as according with the correct symbol and font replacement (substitution) experienced by children can be overcome. Proven thereby formula of is problem of which is told to be answered that method of VAKT effective in overcoming replacement of characters (substitution) at child of intelegance below of class IV in SDLBN 20 Pariaman cities. Relate to result of research in overcoming substitution write start of child of intelegance below X beginning of writing, the researcher suggested to teachers to use method of VAKT for future learning.